CYP2E1-Dependent and Leptin-Mediated Hepatic CD57 Expression on CD8+ve T Cells aid Progression of Environment-Linked Nonalcoholic Steatohepatitis - Seth, Ratanesh Kumar (2013)
Environmental toxins induce a novel CYP2E1/leptin signaling axis in liver. This in turn activates a poorly characterized innate immune response that contributes to nonalcoholic steatohepatitis (NASH) progression. To identify the relevant subsets of T-lymphocytes in CYP2E1-dependent, environment-linked NASH, we utilized a model of diet induced obese (DIO) mice that are chronically exposed to bromodichloromethane. Mice deficient in CYP2E1, leptin (ob/ob mice), or both T and B cells (Pfp/Rag2 double knockout (KO) mice) were used to delineate the role of each of these factors in metabolic oxidative stress-induced T cell activation. Results revealed that elevated levels of lipid peroxidation, tyrosyl radical formation, mitochondrial tyrosine nitration and hepatic leptin as a consequence of metabolic oxidative stress caused increased levels of hepatic CD57, a marker of peripheral blood lymphocytes including NKT cells. CD8+CD57+ cytotoxic T cells but not CD4+CD57+ cells were significantly decreased in mice lacking CYP2E1 and leptin. There was a significant increase in the levels of T cell cytokines IL-2, IL-1β, IFN-γ in bromodichloromethane exposed DIO mice but not in mice that lacked CYP2E1, leptin or T and B cells. Apoptosis as evidenced by TUNEL assay and levels of cleaved caspase-3 was significantly lower in leptin and Pfp/Rag2 KO mice and highly correlated with protection from NASH. The results described above suggest that higher levels of oxidative stress-induced leptin mediated CD8+CD57+ T cells play an important role in the development of NASH. It also provides a novel insight of immune dysregulation and may be a key biomarker in NASH.